2018
DOI: 10.1021/acs.biochem.8b00399
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the Mango-II RNA Aptamer Reveal Heterogeneous Fluorophore Binding and Guide Engineering of Variants with Improved Selectivity and Brightness

Abstract: Several RNA aptamers that bind small molecules and enhance their fluorescence have been successfully used to tag and track RNAs in vivo, but these genetically encodable tags have not yet achieved single-fluorophore resolution. Recently, Mango-II, an RNA that binds TO1-Biotin with ∼1 nM affinity and enhances its fluorescence by >1500-fold, was isolated by fluorescence selection from the pool that yielded the original RNA Mango. We determined the crystal structures of Mango-II in complex with two fluorophores, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 12 publications
(29 reference statements)
2
62
0
Order By: Relevance
“…We chose the Mango II aptamer (Fig. 1a) because of its resistance to formaldehyde fixation, enhanced thermal stability and high affinity for TO1-Biotin (TO1-B) 28,29 . As Mango II requires a closing stem to efficiently fold, we engineered modified stem sequences by altering the Watson-Crick base pairs of three adjacent aptamers to avoid potential misfolding between the aptamer modules ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We chose the Mango II aptamer (Fig. 1a) because of its resistance to formaldehyde fixation, enhanced thermal stability and high affinity for TO1-Biotin (TO1-B) 28,29 . As Mango II requires a closing stem to efficiently fold, we engineered modified stem sequences by altering the Watson-Crick base pairs of three adjacent aptamers to avoid potential misfolding between the aptamer modules ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The open pocket also accommodates the TO3 headgroup, explaining the similar affinity of both fluorophores, 1.1 and 1.3 n M ). Biotin is not present in the ligand binding pocket, and while most of the PEG linker appeared to be excluded from the pocket, it was shown that its interactions with the RNA contribute to affinity and selectivity …”
Section: High Fluorophore Affinity Of Compact Mango Aptamersmentioning
confidence: 98%
“…47,57,58 The structures of Mango variants from generations I-IV are known, and have recently been discussed in detail. 3,[58][59][60][61] The core of all Mango aptamers contains a G-quadruplex, primarily responsible for stacking and rigidification of the bound ligand. While the first generation included the PEG linker and the biotin in packing onto the G-quartet next to TO1, 61 later generations exhibited improved fluorophore planarity resulting in higher brightness.…”
Section: To-binding Aptamers -Mangomentioning
confidence: 99%